Creative thinking ability on the integrating mathematical habits of mind in missouri mathematics project learning. (October 2019) - Mellawaty; Sudirman; Waluya, St B; Rochmad
Abstract: The method in this study, Mixed Method Design with concurrent embedded strategy. This research was conducted mathematical creative thinking skills of students class VII-B of Indramayu State Middle School 1, Academic Year 2018/2019. Sampling technique used snowball sampling technique.There were three stages in this research, the first was designing learning process stage that consisted of syllabus, lesson plan, learning syntax and expert validated test items. The second was the implementation. It was conducted to see the students' respond and activity during the learning process. The third was evaluation stage. This was conducted to know the learning effectiveness. The result, it was obtained that (1) the learning design integrated Mathematical Habits of Mind (MHM) and Missouri Mathematic Project (MMP) consists of syllabus, lesson plan, learning syntax, students' worksheet and TKBKM were valid; (2) The respond of students and teacher were 82, 9% good and happy to involve in the process of learning design that integrates Mathematical Habits of Mind (MHM) and Missouri Mathematic Project (MMP); (3) the learning that integrates Mathematical Habits of Mind (MHM) with Missouri Mathematics Project (MMP) learning is effective in improving mathematical creative thinking students with moderate categories.